Magnesioferrites for solar thermochemical fuel production. (15th March 2018) - Randhir, Kelvin; Rhodes, Nathan R.; Li, Like; AuYeung, Nicholas; Hahn, David W.; Mei, Renwei; Klausner, James F.
Highlights: Mixing iron oxide with magnesium oxide improves stability. Temperatures required for thermal reduction are less than 1450 °C. Partial pressure of oxygen for reduction achievable using industrial vacuum pumps. The hydrogen production capacity is higher than ceria. Abstract: Solid solutions of iron oxide in MgO, prepared using the solid state reaction method (SSR), were investigated for solar thermochemical water splitting/carbon dioxide splitting (STC-WS/CDS). Experimental results show that 20 mole% magnetite (Fe3 O4 ) in MgO has a hydrogen (H2 ) production capacity of 6.12 ± 0.22 cm 3 g −1 total material when thermally reduced at 1450 °C ( T red ) under an inert environment and oxidized at 1200 °C ( T ox ) with excess steam. This compares favorably with cerium dioxide (CeO2 ), which has proven to be an excellent STC-WS/CDS material, with H2 production 2.91 ± 0.15 cm 3 g −1 total material at T red = 1450 °C and T ox = 1200 °C, and 4.34 ± 0.2 cm 3 g −1 total material at T red = 1500 °C and T ox = 1200 °C. 20 mole% Fe3 O4 in MgO has advantages of lower operating temperature and higher production capacity. The partial pressure of oxygen (PO2 ) during thermal reduction is on the order of 10 −4 atm, which can be achieved using existing industrial vacuum pump technology. These advantages make this material a viable option for further study in solar thermochemical fuel production applications.